(untitled) (Journal of Engineering, 2025)
This study evaluates the hydraulic performance of Baghdad’s water supply network by analysing pressure heads and velocities. In this work, Water-CAD hydraulic models integrated with QGIS were utilized. The districts 821 and 835 were selected in partnership with Al-Rashid Municipality Water Department, two districts fed from a single source, with the construction period of the two networks differing. They were calibrated in Darwin calibration using field-measured pressure at five and three locations, respectively, achieving coefficient of determination (R²) = 0.99. In District 821, pressure analysis during peak demand revealed that most junctions operated under 7 m H₂O, with 14% exhibiting negative pressure and 84% below this threshold. Velocity analysis showed that 94% of pipes-maintained velocities below 0.5 m/s, 5.6% operated between 0.5–2 m/s, and 0.5% exceeded 2 m/s. At low demand, more than half of the junctions recorded pressure heads below 7 m H₂O, while 25% exceeded this value. Velocity levels during low demand do not have considerable variations compared with peak hours usage. In district 835, all junctions recorded pressures below 7 m H₂O during peak demand, with about 50% experiencing negative pressure. Low demand analysis indicated 80 junctions operated below 7 m H₂O, while 27 exceeded this criterion. Velocity analysis revealed that 83% of pipes operated below 0.5 m/s, with the remaining 17% within 0.5–2 m/s. In conclusion, both networks predominantly operated below the acceptable pressure head of 7 m H₂O, highlighting insufficient water supply to consumers, particularly during peak demand periods.